2020
DOI: 10.1111/bph.14886
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone alleviates intrahepatic cholestasis induced by α‐naphthylisothiocyanate in mice: The role of circulating 15‐deoxy‐Δ12,14‐PGJ2 and Nogo

Abstract: Background and Purpose Intrahepatic cholestasis is mainly caused by dysfunction of bile secretion and has limited effective treatment. Rosiglitazone is a synthetic agonist of PPARγ, whose endogenous agonist is 15‐deoxy‐Δ12,14‐PGJ2 (15d‐PGJ2). Reticulon 4B (Nogo‐B) is the detectable Nogo protein family member in the liver and secreted into circulation. Here, we determined if rosiglitazone can alleviate intrahepatic cholestasis in mice. Experimental Approach Wild‐type, hepatocyte‐specific PPARγ or Nogo‐B knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
4
19
0
Order By: Relevance
“…Consistent with previous studies (Zhang et al, 2020), ANIT treatment alone resulted in the accumulation of bile acids in the liver and serum of mice, and reduced bile acid contents in the faeces, which suggested that bile flow was mainly obstructed from the liver to the intestine (Figure 3a). CLD in mice was associated with reduced hepatic gene expression of canalicular transporters of bile salts (BSEP encoded by Abcb11 ), bilirubin (ABCC2, encoded by Abcc2 ), and phytosterols (ABCG5 and ABCG8, encoded by Abcg5 and Abcg8 )(El Kasmi et al, 2018; Yang et al, 2019; Zhang et al, 2020). Consistent with biochemical cholestasis, mRNA expression of export transporters ( Abcc2 and Bsep ), phytosterol transporters ( Abcg5 and Abcg8 ), and uptake transporters ( Ntcp and Oatp1 ) were significantly suppressed in mice with ANIT‐induced CLD (Figure 3b).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (Zhang et al, 2020), ANIT treatment alone resulted in the accumulation of bile acids in the liver and serum of mice, and reduced bile acid contents in the faeces, which suggested that bile flow was mainly obstructed from the liver to the intestine (Figure 3a). CLD in mice was associated with reduced hepatic gene expression of canalicular transporters of bile salts (BSEP encoded by Abcb11 ), bilirubin (ABCC2, encoded by Abcc2 ), and phytosterols (ABCG5 and ABCG8, encoded by Abcg5 and Abcg8 )(El Kasmi et al, 2018; Yang et al, 2019; Zhang et al, 2020). Consistent with biochemical cholestasis, mRNA expression of export transporters ( Abcc2 and Bsep ), phytosterol transporters ( Abcg5 and Abcg8 ), and uptake transporters ( Ntcp and Oatp1 ) were significantly suppressed in mice with ANIT‐induced CLD (Figure 3b).…”
Section: Resultssupporting
confidence: 92%
“…At 2 weeks after infection, the mice were used for experiments, as described above. Extraction and determination of total bile acids (TBA) in mouse liver and intestine was performed as previously reported (Zhang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…TEC rescued bile metabolic dysfunction in mice with intrahepatic cholestasis induced by ANIT or DDC We then undertook experiments to verify bile metabolism after TEC intervention in the CLD experimental model. Consistent with previous studies [29] , ANIT treatment alone resulted in the accumulation of bile acids in the liver and serum of mice, and reduced the content of bile acids in feces, which suggested that bile flow was mainly obstructed from the liver to the intestine (Figure 3A). CLD in mice was associated with reduced hepatic gene expression of canalicular transporters of bile salts (Bsep encoded by Abcb11), bilirubin (Mrp2, encoded by Abcc2), and phytosterols (the heterodimer sterolin1 and sterolin2, encoded by ABCG5 and ABCG8) [20,29,30] .…”
Section: Tec Alleviated Anit-induced and Ddc-induced Experimental Intrahepatic Cholestasissupporting
confidence: 91%
“…Consistent with previous studies [29] , ANIT treatment alone resulted in the accumulation of bile acids in the liver and serum of mice, and reduced the content of bile acids in feces, which suggested that bile flow was mainly obstructed from the liver to the intestine (Figure 3A). CLD in mice was associated with reduced hepatic gene expression of canalicular transporters of bile salts (Bsep encoded by Abcb11), bilirubin (Mrp2, encoded by Abcc2), and phytosterols (the heterodimer sterolin1 and sterolin2, encoded by ABCG5 and ABCG8) [20,29,30] . Concomitant with biochemical cholestasis, mRNA expression of export transporters (Mrp2 and Bsep), phytosterol transporters (ABCG5 and ABCG8) and uptake transporters (Ntcp, Oatp) were significantly suppressed in mice with ANIT-induced CLD (Figure 3B).…”
Section: Tec Alleviated Anit-induced and Ddc-induced Experimental Intrahepatic Cholestasissupporting
confidence: 91%
See 1 more Smart Citation